2010
DOI: 10.1039/b913338k
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of micropollutant estrone to a water treatment ion exchange resin

Abstract: Micropollutants occur in natural waters from a range of sources. Estrogenic compounds are naturally excreted by humans and hence stem predominantly from wastewater effluents. Due to their small molecular weight and concentration their effective control is a challenge. In this study magnetic ion exchange (MIEX), which was developed to remove natural organic matter (NOM) from surface water, was investigated for such a micropollutant, estrone. The interaction of estrone with the resin occurs as a side effect when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Previous investigations have demonstrated the efficient adsorption of estrone (Zhang and Zhou, 2005;Neale et al, 2010), SMX (Choi et al, 2007;Huang et al, 2011;Fern andez et al, 2014), TC (Choi et al, 2007), and NPX (Landry et al, 2015) onto AERs in batch tests, which was also demonstrated during the first cycle in this study. In fact, AER treatment removed almost all of the microconstituents, regardless of their predominant existing forms, during short-term cyclical operation (i.e., the 1st adsorptionregeneration cycle) in this study.…”
Section: Strong-base Aer (D201)supporting
confidence: 67%
See 2 more Smart Citations
“…Previous investigations have demonstrated the efficient adsorption of estrone (Zhang and Zhou, 2005;Neale et al, 2010), SMX (Choi et al, 2007;Huang et al, 2011;Fern andez et al, 2014), TC (Choi et al, 2007), and NPX (Landry et al, 2015) onto AERs in batch tests, which was also demonstrated during the first cycle in this study. In fact, AER treatment removed almost all of the microconstituents, regardless of their predominant existing forms, during short-term cyclical operation (i.e., the 1st adsorptionregeneration cycle) in this study.…”
Section: Strong-base Aer (D201)supporting
confidence: 67%
“…This is in agreement with previous observations by Huang et al (2011), who found that the compounds with substantial removal by AER treatment at pH 8.0 had a broad pK a range of 1.7e10.1. Neale et al (2010) also found that AER treatment removed around 70% of estrone (pK a 10.4) at pH > 10.4 or approximately 40% of estrone at pH < 10.4. In this study, the presence of complex non-electrostatic interactions ensured the effective adsorption of all 12 pharmaceuticals onto AER during short-term cyclical operation.…”
Section: Strong-base Aer (D201)mentioning
confidence: 87%
See 1 more Smart Citation
“…For example, magnetic ion exchange resin (MIEX) developed for enhanced natural organics removal, sorbs significant amounts of uncharged micropollutants such as estrogens [161]. The resin has a macroporous polyacrylate shell with quaternary ammonium functional groups for ion exchange.…”
Section: Micropollutant Sorption By Different Polymer Materialsmentioning
confidence: 99%
“…For anionic chemicals, such as bentazone and 2,4-dichlorophenoxyacetic acid [74][75][76], MIEX resin shows high removal up to 99 %, whereas for non-ionic chemicals, such as atrazine and isoproturon, MIEX resin shows negligible removal [33]. MIEX resin removed approximately 40 % of estrone at pH 8 (neutral molecule) and removal increased to approximately 70 % at pH 12 where estrone is negatively charged [77]. MIEX resin showed 0-48 % removal of 15 commonly detected pharmaceuticals and personal care products with higher removal observed for negatively charged species [78].…”
Section: Synthetic Organic Chemicalsmentioning
confidence: 99%